Formación y prácticas pedagógicas en educación intercultural bilingüe en docentes de las instituciones educativas de nivel inicial de Caballococha 2024 - Sinojara Tello, Beatriz (2025)
The present study aimed to establish the relationship between teacher training and pedagogical practices in bilingual intercultural education among educators in early childhood education institutions in Caballococha in 2024. The research included a population of 71 administrators and teachers from various educational institutions, with this group selected as a representative sample. Methodologically, a relational approach was adopted with a cross-sectional and bivariate research design. For data collection, two questionnaires were used, applying the survey technique. The results revealed that the obtained p-value (p = .000) was below the significance threshold of .05, which allowed for the rejection of the null hypothesis (H0), which postulated the absence of a significant relationship between teacher training and pedagogical practices in bilingual intercultural education. Additionally, the Spearman correlation coefficient (rho = .460) indicated a positive and moderate relationship between the quality of teacher training and the implementation of effective pedagogical practices in this field. In conclusion, it is evident that adequate training in bilingual intercultural education is significantly associated with the improvement of pedagogical practices in this educational context, highlighting the importance of strengthening educators' training to optimize the teaching and learning process in intercultural environments.